(untitled) (CIPEEX, 2025)
COPD, a chronic respiratory condition associated with an increased risk of kidney failure, affects a significant portion of the adult population in Brazil and is one of the leading causes of hospitalization and mortality. The management of severe COPD includes medications and nutritional interventions, with an emphasis on protein intake to preserve muscle mass and improve lung function. This study aims to evaluate the relationship between nutritional status and renal alterations in patients with severe COPD, as well as to investigate the effects of supplementation with Whey Protein and hydrolyzed collagen on renal function in these patients. A total of 150 participants will be recruited, divided into control, Whey Protein, or collagen-supplemented groups, with assessments conducted before and after the intervention, aiming to explore the market potential of these supplements in the treatment of severe COPD.